ELECTRONIC SIGNATURE, ELECTRONIC SEAL AND ELECTRONIC TIMESTAMP – PLACE AND ROLE IN CROATIAN LEGISLATION - Nika Terze (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
With the new legislative framework in the Republic of Croatia, the terms electronic list, electronic seal and electronic time stamp are given a central role in the activities of state authorities, other state bodies, local and regional (regional) self-government units and legal entities with public powers, i.e. public law bodies. However, the question arises as to how ready the aforementioned bodies are to transform their current work model and adapt to the changes introduced by the new legislative framework. The prerequisites for the aforementioned legislative changes were set by the European Union through its legislation, which is mandatory in all member states. Also, one of the biggest challenges that appears is the lack of knowledge of the aforementioned legislative framework, its provisions and the meaning, i.e. the legal force of the terms electronic signature, electronic seal and time stamp. Accordingly, in this paper author will explain in more detail their meaning within the framework of the legislation of the European Union and the Republic of Croatia.